Hubungan Perilaku Asertivitas dengan Kepuasan Pernikahan pada Pasutri Beretnis Minang - Erwinda, Dewi Yuni; Adri, Zakwan (Lembaga Yasin AlSys, 2023)
Marriage is the most important experience in life, because of that every couple definitely wants a happy marriage once in a lifetime. One of the things that affect marital satisfaction is because of assertive communication. So, the purpose of this study was to see the relationship between assertiveness and marital satisfaction for Minang ethnic couples. This study used a quantitative method, the study population was a married couple with Minang ethnicity using a purposive sampling technique. There were 212 samples in this study consisting of 106 married couples. The study used the Maritime Satisfaction and Assertiveness scale with the reliability of both variables 0.946 and 0.927. The data analysis technique uses product moment correlation with the help of SPSS Statistics 20 for windows. The results of hypothesis testing r = 0.146 and p = 0.033, it is known that there is a significant positive relationship between Assertiveness behavior and Marital Satisfaction in married couples with Minang ethnicity.